The amenity value of the Italian climate - David Maddison; Andrea Bigano (Fondazione Eni Enrico Mattei (FEEM), 1997)
The hedonic literature suggests that locations with more favourable characteristics should display compensating wage and residential land price differentials. Using the hedonic price technique estimates of the willingness to pay for small changes in some key characteristics of the Italian climate were undertaken. The hedonic price models were specified both in terms of annual values and in terms of monthly values. The main conclusion of the analysis is that there exists considerable empirical support to the hypothesis that amenity values for climate are embedded in residential property prices. Italians would typically prefer a dryer, sunnier climate than at present, warmer in the winter and slightly cooler during the summer. The existence of compensating wage differentials was not investigated. These results may have relevance to the task of determining the economic impact of potential future climate change.
Keywords: 330; Climate Change; Italy; Hedonics; Klimawandel; Hedonischer Preisindex; Willingness to pay; Italien